Fuzzy –Super twisting control implementation of battery/super capacitor for electric vehicles - M. Sellali; S. Abdeddaim; A. Betka; A. Djerdir; S. Drid; M. Tiar (ISA transactions, 2019)
The present paper deals with a real-time implementation of a novel Fuzzy logic energy management strategy (EMS), applied to a battery–super capacitor hybrid energy system and associated with a permanent magnet synchronous motor (PMSM) which emulates the traction part of an electric vehicle (EV). On the sources side, the fuzzy logic supervisor acts in a smart way to permute smoothly between the various operations modes via an efficient power frequency splitting. In addition, it permits a quite regulation of both the DC bus and the super-capacitor (SC) voltages regardless of the speed profile variations to ensure an optimal power flow to the load and to keep the SC operation in a safe voltage range while providing or absorbing power in transients. On the traction side, a second order sliding mode control called ‘super-twisting’ (ST), associated with a space vector modulation (SVM) strategy is applied to ensure …